Implementation and in-depth analyses of a battery-supercapacitor powered electric vehicle (E-Kancil) - Embrandiri, Manoj (2014)
This thesis contributes to the research issue pertaining to the management of multiple energy sources on-board a pure electric vehicle; particularly the energy dense traction battery and the power dense supercapacitor or ultracapacitor. This is achieved by analysing real world drive data on the interaction between lead acid battery pack and supercapacitor module connected in parallel while trying to fulfil the load demands of the vehicle. The initial findings and performance of a prototype electric vehicle conversion of a famous Malaysian city car; the perodual kancil, is presented in this thesis. The 660 cc compact city car engine was replaced with a brushless DC motor rated at 8KW continuous and 20KW peak. The battery pack consists of eight T105 Trojan 6V, 225 Ah deep cycle lead acid battery which builds up a voltage of 48V. In addition to this, a supercapacitor module (165F, 48V) is connected in parallel using high power contactors in order to investigate the increase in performance criteria such as acceleration, range, battery life etc. which have been proven in various literatures via simulation studies. A data acquisition system is setup in order to collect real world driving data from the electric vehicle on the fly along a fixed route. Analysis of collected driving data is done using MATLAB software and comparison of performance of the electric vehicle with and without supercapacitor module is made. Results show that with a parallel connection, battery life and health is enhanced by reduction in peak currents of up to 49%. Peak power capabilities of the entire hybrid source increased from 9.5KW to 12.5KW. A 41% increase in range per charge was recorded. The author of this work hopes that by capitalizing on the natural peak power buffering capabilities of the supercapacitor, a cost effective energy management system can be designed in order to utilize more than 23.6% of the supercapacitor energy.